Pengaruh Pengetahuan Kewirausahaan, Strategi Pemasaran Dan Lokasi Usaha Terhadap Keberhasilan UMKM (Studi Kasus Pada Pengrajin Perak Kotagede, Yogyakarta) - Muhammad Alfiannur; Beni Suhendra Winarso (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2023)
This study examines the "Effect of entrepreneurial knowledge, marketing strategy and business location on the success of MSME business (case study on silver craftsmen Kotagede Yogyakarta)". The independent variables used are entrepreneurial knowledge, marketing strategy, business location, and business success variables. The Quantitative approach was used in this research to gather the data. The method used is multiple linear regression processed using SPSS. The results of this study indicate that the entrepreneurial knowledge variable affects business success, the marketing strategy variable affects business success, location variable affects business success. Simultaneously, entrepreneurial knowledge, marketing strategy, and business location affect business success.